PERSPECTIVES OF TRADITIONAL HEALTH PRACTITIONERS ON THE USE OF MICROBICIDES FOR THE PREVENTION OF HIV - Walwyn, David; Maitshotlo, Boitumelo (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
In many South African communities, Traditional Health Practitioners (THPs) are significant participants within a plural health care system. For several years, it has been argued that this role, especially in the context of HIV/AIDS, has not been fully optimised and THPs continue to operate outside the formal biomedical sector, where the latter forms the central means by which public health campaigns are delivered and implemented. In our previous research, we have shown that this separation of the biomedical and traditional sectors perpetuates a low level of understanding of HIV by THPs with adverse consequences for patients and the overall health care system. In this study we investigated whether biomedical/traditional division could be transformed through the involvement of THPs in the distribution of barrier microbicides; the latter are presently under investigation as a means of preventing HIV infection. We concluded that THPs could provide a willing and effective distribution network for the gel-based microbicides; given the large number of THPs and their patients, such a distribution strategy would ensure that microbicides are accessible and adopted relatively quickly within the target communities of the HIV prevention campaigns.